2022
DOI: 10.1139/tcsme-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the effect of hole reaming on fatigue life by cold expansion

Abstract: The reaming process of the 6061 aluminum alloy plate after cold expansion with split sleeve was simulated by finite element (FE) method based on Abaqus/CAE, the relationship between the reaming depths and the distribution of residual stress fields is obtained by analysis. The fatigue lives of the plate under different reaming depths were calculated by using the fatigue analysis software FE-SAFE, and verified by fatigue tests. The results show that reaming after expansion will increase the residual compressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Proper reaming of the hole wall can correct the roundness of the hole and remove potential fatigue micro-cracks, ensure the continuity of hole collection and micro-continuity, and improve the fatigue life of the hole [57]. However, the removal of the material will inevitably change the elastic-plastic state of the pore wall material, thereby affecting residual stress and microstructure, as shown in Figure 7c [58]. Figure 7d shows the effect of different reaming amounts on the residual stress distribution.…”
Section: Reamingmentioning
confidence: 99%
“…Proper reaming of the hole wall can correct the roundness of the hole and remove potential fatigue micro-cracks, ensure the continuity of hole collection and micro-continuity, and improve the fatigue life of the hole [57]. However, the removal of the material will inevitably change the elastic-plastic state of the pore wall material, thereby affecting residual stress and microstructure, as shown in Figure 7c [58]. Figure 7d shows the effect of different reaming amounts on the residual stress distribution.…”
Section: Reamingmentioning
confidence: 99%
“…The results show that the maximum values of circumferential residual compressive/tensile stresses in both the "infinite" and "finite" domains increase with the development of the interference values, and higher values of positive stresses are obtained at the boundary of the "finite" domain [24][25][26][27]. In addition to this, the main parameters affecting bushing repair can be analyzed qualitatively based on fatigue theory [28][29][30][31]. The results showed that the fatigue quality of the bushing decreases with the increase in the bushing's outer diameter.…”
Section: Introductionmentioning
confidence: 99%